Heterosis on morphological, reproductive and productive behavior of Acroceras macrum Stapf hybrids - Ferrari Usandizaga, Silvana Consuelo; Brugnoli, Elsa Andrea; Maidana, Carlos Emilio; Martinez, Eric Javier; Acuña, Carlos Alberto (Springer, 2024)
Acroceras macrum, a forage grass from Africa, offers potential for enhancing cattle production in subtropical flood-prone regions. Despite its use in Northeast Argentina since the 1980s, the lack of available fertile seeds limits its widespread adoption and large-scale cultivation. We evaluate a germplasm collection of hybrids generated for breeding purposes in Corrientes, Argentina. To assess the feasibility of breeding programs, we examined heterosis and heritability through phenotypic traits. We evaluated growth characteristics (initial vigor, ground cover), plant morphology (leaf and internode size), biomass production (across two sites and years), reproductive stem proportion, flowering peak timing, and seed filling (measured on four dates). Six families were assessed: four full-sibling families compared to the superior parent, and two half-sibling families. The timing of the flowering peak exhibited a correlation with photoperiod. All traits depended on parental combinations, exhibiting significant intra-familial variability ranging from negative heterotic hybrids exceeding 80% to positive hybrids reaching 90%. Correlations between heterosis of the traits and parents’ genetic distance must be confirmed. Nevertheless, correlativeness was mainly observed for biomass production for distinct years and seasons. Hence, genetic distance could be a useful tool for the election of the parental combinations to improve this key trait in the species. Furthermore, heritability, was significant for most evaluated traits. It also could be exploited for breeding. This comprehensive assessment sheds light on the phenotypic behavior of A. macrum families, providing valuable insights for future breeding efforts aimed at enhancing its agronomic potential in subtropical regions prone to flooding.